Performing Tradition: History, Expression, and Meaning in Drum Corps Shows. (14th March 2016) - Odello, Denise
Abstract : The performances of youth drum corps in the United States reference both the history of the activity and the past practices of individual ensembles. These references create an insular form of performance where only cultural insiders who are familiar with both drum corps tradition and the performance histories of individual organizations are able to fully understand a performance. This article will examine four performances from the 2012 season in order to unravel these references. Participants disagree on how large a role tradition should play in shaping these performances, so performance choices become both aesthetic and political statements.